2020
DOI: 10.3390/app10072499
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Heavily Doped n+ Pocket Asymmetrical Junction-Less Double Gate MOSFET for Biomedical Applications

Abstract: The Complementary Metal-Oxide Semiconductor (CMOS) technology has evolved to a great extent and is being used for different applications like environmental, biomedical, radiofrequency and switching, etc. Metal-Oxide-Semiconductor Field-Effect Transistor (MOSFET) based biosensors are used for detecting various enzymes, molecules, pathogens and antigens efficiently with a less time-consuming process involved in comparison to other options. Early-stage detection of disease is easily possible using Field-Effect Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been reported that for the negatively (positively) charged biomolecules, n-type (p-type) JL-DM-DG-MOSFET shows better sensitivity. Mendiratta et al [ 14 ] studied the sensing performance of an n + pocket asymmetrical junctionless DG-MOSFET-based biosensor. The proposed biosensor can be used for detecting diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that for the negatively (positively) charged biomolecules, n-type (p-type) JL-DM-DG-MOSFET shows better sensitivity. Mendiratta et al [ 14 ] studied the sensing performance of an n + pocket asymmetrical junctionless DG-MOSFET-based biosensor. The proposed biosensor can be used for detecting diseases.…”
Section: Introductionmentioning
confidence: 99%